Educators in preschools develop their practice with young children - Sigurðardóttir, Ingibjörg Ósk; Pálmadóttir, Hrönn (Menntavísindasvið Háskóla Íslands, 2024)
In Iceland, the composition of preschool children’s groups has changed considerably over recent years, and today, over fifty per cent of children under age two attend preschool. These first years are crucial for future life learning. However, previous studies show preschool educators need improved knowledge about the youngest children and how they express themselves. Therefore, it is important to promote greater knowledge and professional development for educators working with the youngest children in preschools. Furthermore, studies show that professionalism and professional development of preschool staff are crucial factors regarding quality in practice. This research aimed to study preschool teachers and other staff members’ experiences participating in action research to promote professional development and professionalism in preschool practices with young children. In the study, professional development is seen as formal and informal education that deepens and improves teacher competencies and knowledge. Professional development is related to daily practices, leading to improvements and development. Previous studies show that the action research methodology is effective for teacher professional development and school practice improvement. This methodology has also proven effective in creating understanding and bringing it forward in the preschool community. The main challenges that participants face during the research process are lack of time and influence on colleagues who are not part of the process. The action research studied here continued for four years. It was conducted in six departments in three preschools, where the children ranged in age from nine months to two and a half years. The research emphasised creating a learning community among department educators, preschool leaders, and researchers from the University of Iceland. The role of the researchers was to support the participants through the rocess and mediate new knowledge in early childhood education and action research. The principal of ...